Archive Mining Brings to Light a 25-Year Old Astrovirus Encephalitis Case in a Sheep - Küchler, Leonore; Koch, Michel C.; Seuberlich, Torsten; Boujon, Céline L. (Frontiers in Veterinary Science, 2019)
In mammals, the small, positive-sense single-stranded RNA astroviruses are known as being mostly enterotropic and host-specific. Over the past years, however, they were identified several times in central nervous system tissues of humans, minks, cattle, sheep and pigs with nonsuppurative inflammatory disease of that organ system. We recently reported such neurotropic astroviruses, amongst which bovine astrovirus CH15 (BoAstV-CH15) in two cows, and ovine astrovirus CH16 (OvAstV-CH16) in a sheep, which were genetically almost identical to one another. In order to investigate the occurrence of this virus species in Switzerland over time, we selected formalin-fixed, paraffin-embedded (FFPE) brain tissues of small ruminants diagnosed with severe encephalitis between 1969 and 2012 and screened those by immunohistochemistry for the capsid protein of BoAstV-CH15/ OvAstV-CH16. We found one sheep, which died in 1992, that displayed positive immunostaining in various brain regions, and observed that immunostained cells were generally co-localized with the strongest histopathological lesions. We confirmed the virus presence with a second immunohistochemical protocol and demonstrated its close genetic relationship to other BoAstV-CH15/ OvAstV-CH16 strains by next-generation sequencing of an RNA extract from FFPE brain material. Our findings demonstrate that astrovirus BoAstV-CH15/ OvAstV-CH16 existed in Switzerland already more than two decades ago and underline again the close relationship of the bovine and ovine strains of this virus.